2022
DOI: 10.1038/s41598-022-17629-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of extracellular vesicles from Lactiplantibacillus plantarum

Abstract: We investigated the characteristics and functionalities of extracellular vesicles (EVs) from Lactiplantibacillus plantarum (previously Lactobacillus plantarum) towards host immune cells. L. plantarum produces EVs that have a cytoplasmic membrane and contain cytoplasmic metabolites, membrane and cytoplasmic proteins, and small RNAs, but not bacterial cell wall components, namely, lipoteichoic acid and peptidoglycan. In the presence of L. plantarum EVs, Raw264 cells inducibly produced the pro-inflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
(65 reference statements)
2
24
0
1
Order By: Relevance
“…The particle sizes of LpEVs and GA-LpEVs were determined using DLS, which was approximately 126 and 173 nm, respectively (Figure D). As shown in Figure E, the TEM images revealed that LpEVs exhibited a typical round or cup-shaped morphology, consistent with the previous research. , After GA modification, the GA-LpEVs exhibited a similar structure. The SEM images also demonstrated the spherical morphologies of both LpEVs and GA-LpEVs (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…The particle sizes of LpEVs and GA-LpEVs were determined using DLS, which was approximately 126 and 173 nm, respectively (Figure D). As shown in Figure E, the TEM images revealed that LpEVs exhibited a typical round or cup-shaped morphology, consistent with the previous research. , After GA modification, the GA-LpEVs exhibited a similar structure. The SEM images also demonstrated the spherical morphologies of both LpEVs and GA-LpEVs (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed the protective effect of probiotic EVs on atopic dermatitis [ 139 ] and various intestinal pathologies (chemoresistant colorectal cancer [ 140 ] or intestinal infections made by enterotoxigenic E. coli [ 141 ]). It was also noticed that probiotic EVs have a strong immunomodulatory effect on the human body (including the intestines) [ 142 ], and that they can be used in the design of innovative vaccines against infectious diseases [ 143 ] and cancers [ 122 ]. In the last publication, attention was drawn to the participation of prophages in the secretion of EVs by the tested probiotic bacteria [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by how L. plantarum EVs cause the decrease of proinflammatory cytokine IL-6 induced by S. aureus EVs in immune cells and skin cells (103). Notably, despite being probiotic and providing benefits to the host, not all Lactobacillus bacteria have anti-inflammatory properties, as L. plantarum EVs induce not only the anti-inflammatory cytokine IL-10 but also the proinflammatory cytokines IL-1β and IL-6 to activate the host immune system (101). Furthermore, L. plantarum EVs potentially use proteomic sections of Lp19180, a lipoprotein found in the cellular membrane, as a ligand of TLR2 to induce the NF-κB pathway (101).…”
Section: Manipulation Of Anti-inflammatory Tlr Pathways and Cytokine ...mentioning
confidence: 99%